Ugi-Type Reactions of Spirocyclic Indolenines as a Platform for Compound Library Generation - Estévez, Verónica; Kloeters, Laura; Kwietniewska, Natalia; Vicente-García, Esther; Ruijter, Eelco; Orru, Romano V. A. (Synlett, 2017)
A simple and efficient method for the synthesis of highly substituted spiroindoline derivatives is presented. A Fischer indolization is combined with Ugi-type reactions to explore the chemical space concerning this privileged structure. Moreover, spiropiperidine derivatives could be postmodified for the production of a small-molecule library that will be part of the Joint European Compound Library of the European Lead Factory.
Keywords: scaffold; spiroindoline; Ugi-type reaction; compound library